The Application of Differentiated Learning to the Creative Thinking Abilities of Elementary School Students - Wulan pratiwi (AIQU: Journal Multidiscipliner of Science, 2024)
The level of creativity in Indonesia is still relatively low. One of the reasons is that educational institutions have not been able to adequately meet the needs of diverse students, which have been recognized by the government. The curriculum at Merdeka is identical to the differentiated de cension method. It is hoped that it will be able to accommodate community needs. learn students. The aim of this research is to understand the influence of differentiated learning on creative thinking, as well as the factors that cause an increase in creative thinking after differentiated learning is implemented in elementary schools. This research uses a systematic literature review (SLR) methodology which consists of five steps: identifying relevant literature, identifying problems, obtaining research results that are in line with quality assessments (screening and eligibility), and analyzing research findings from articles.